2022
DOI: 10.1007/s00044-022-02903-0
|View full text |Cite
|
Sign up to set email alerts
|

Invalidation of dieckol and 1,2,3,4,6-pentagalloylglucose (PGG) as SARS-CoV-2 main protease inhibitors and the discovery of PGG as a papain-like protease inhibitor

Abstract: The COVID-19 pandemic spurred a broad interest in antiviral drug discovery. The SARS-CoV-2 main protease (M pro ) and papain-like protease (PL pro ) are attractive antiviral drug targets given their vital roles in viral replication and modulation of host immune response. Structurally disparate compounds were reported as M pro and PL pro inhibitors from either drug repurposing or rational design. Two polyphenols dieckol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…These proteases and many others contain catalytic cysteine residues that are crucial for enzymatic function [ 121 , 122 ]. Because disulfiram is known to bind and covalently modify these residues, researchers have investigated its ability to inhibit coronavirus activity [ 20 , 121 , 123 , 124 , 125 , 126 , 127 ]. In 2018, one in vitro study found that disulfiram inhibited proteases in the MERS-CoV and SARS-CoV-1 coronavirus strains [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These proteases and many others contain catalytic cysteine residues that are crucial for enzymatic function [ 121 , 122 ]. Because disulfiram is known to bind and covalently modify these residues, researchers have investigated its ability to inhibit coronavirus activity [ 20 , 121 , 123 , 124 , 125 , 126 , 127 ]. In 2018, one in vitro study found that disulfiram inhibited proteases in the MERS-CoV and SARS-CoV-1 coronavirus strains [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…The evidence is mixed as to whether disulfiram inhibits papain-like protease (PL pro ), an essential enzyme involved in the generation of the replicase complex. One 2020 study found that disulfiram inhibits SARS-CoV-2 by binding to cysteine in PL pro [ 126 ], whereas a 2022 study found that disulfiram had no inhibitory activity against PL pro [ 127 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hence, we believe an investigation into its ability to inhibit human cysteine proteases is warranted as this will likely result in adverse side‐effects. Subsequently, disulfiram was found to be inactive (IC 50 >10 μM) in a cellular SARS‐CoV‐2 PL pro inhibition assay by Rutgers University and The University of Arizona researchers in a 2022 academic paper [88] . Based on this, we opine disulfiram lacks sufficient potency for further development as an antiviral for treating COVID‐19.…”
Section: Patent Reviewmentioning
confidence: 87%
“…Hence, further investigation into its ability to inhibit human cysteine proteases is warranted as this may cause adverse side‐effects. Interestingly, tideglusib was later reported to be inactive (IC 50 >60 μM) in a cell‐based SARS‐CoV‐2 PL pro inhibition assay conducted by Rutgers University and The University of Arizona researchers in a 2022 journal publication [88] …”
Section: Patent Reviewmentioning
confidence: 99%
“…The target selectivity and cellular target engagement of purported M pro inhibitors were addressed by several recent investigations using a variety of secondary assays. 61 , 111 , 112 The compounds can be tested for their ability to inhibit unrelated cysteine proteases, such as the viral EV-A71 2A pro and EV-D68 2A pro , the host cathepsins B, L, and K, caspases, and calpains I, II, and III, among others, to determine their ability to specifically target M pro . Most of the time, substances that block numerous cysteine proteases are promiscuous substances that might act by causing protein aggregation, redox cycling, or alkylating the catalytic cysteine residue Cys145.…”
Section: The Validation Of M Pro Inhibitorsmentioning
confidence: 99%